(untitled) (SOUTH ARAL SEA MEDICAL JOURNAL, 2025)
This study included 70 children hospitalized with acute respiratory infection (ARI) symptoms who underwent PCR testing of upper respiratory tract samples. Viral pathogens were identified in 21 (30.0%) children, with monoinfections in 14 (20.0%) and coinfections in 7 (10.0%). Bocavirus and metapneumovirus were the most frequently detected agents. The findings confirm the clinical significance of PCR diagnostics in pediatric practice.